Asuhan Mandiri Tanaman Obat Keluarga (TOGA) dalam Upaya Peningkatan Kesehatan Masyarakat Kecamatan Banyudono, Boyolali - Reni Ariastuti; Vitri Dyah Herawati (STIFA Makassar, 2019)
Abstract Self care utilization of family medicinal plants (“toga”) is one of the government programs to realize the independence of drugs in the family environment in accordance with Minister of Health Regulation No. 9 of 2016. so many people who do not know enough about the “toga” and its use. Therefore this research was conducted with the aim of wanting to see the profile of Asman toga in the community in the Banyudono sub-district of Boyolali Regency. Sampling was carried out using random sampling method with observational descriptive data collection methods using questionnaire aids and interviews directly to respondents as supporting data. Data analysis was evaluated qualitatively based on the results of questionnaire and interview answers. Banyudono people use a part of the yard to plant the toga. The use of toga is generally for preventive, curative, and promotive purposes. Banyudono people tend to use toga to treat minor illnesses such as coughs, flu, diarrhea and headaches for cheap, easy to obtain and natural reasons. Toga is effective enough to overcome the problem of minor ailments and health promotion, and is able to increase the independence of the family for drugs.